Park location affects forest protection: Land characteristics cause differences in park impacts across Costa Rica - Pfaff, Alexander; Juan A. Robalino; Sanchez-Azofeifa, G. Arturo; Andam, Kwaw S.; Ferraro, Paul J. (Walter de Gruyter GmbH, 2009)
To support conservation planning, we ask whether a park's impact on deforestation rates varies with observable land characteristics that planners could use to prioritize sites. Using matching methods to address bias from non-random location, we find deforestation impacts vary greatly due to park lands' characteristics. Avoided deforestation is greater if parks are closer to the capital city, in sites closer to national roads, and on lower slopes. In allocating scarce conservation resources, policy makers may consider many factors such as the ecosystem services provided by a site and the costs of acquiring the site. Pfaff and Sanchez 2004 claim impact can rise with a focus upon threatened land, all else equal. We provide empirical support in the context of Costa Rica's renowned park system. This insight, alongside information on eco-services and land costs, should guide investments.